Life threatening adverse reaction following prostaglandin analogue use in obstetric and gynecological practice - Anitha Prashanth; Murali Chakravarthy; Pavani Maddirala (Wolters Kluwer Medknow Publications, 2016)
Prostaglandin analogues are the most commonly used drugs by the obstetricians because of its favorable actions on the uterus and cervix. Although considered safe, this drug is associated with various adverse side effects. Here, we report two cases that became hemodynamically unstable after the administration of this drug.